Food remittances : migration and food security in Africa - Crush, Jonathan, 1953-; Caesar, Mary (Migration policy series, 2016)
There is considerable evidence from across the African continent that a significant proportion of cash remittances to rural areas is spent on food. However, bidirectional food remitting -- its drivers, dimensions and impacts -- is an underdeveloped research and policy area. This report therefore reviews the current state of knowledge about food remittances in Africa and aims to make a number of contributions to the study of the relationship between migration and food security.